Crisaborole and its potential role in treating atopic dermatitis: overview of early clinical studies. (July 2016) - Zane, LT; Chanda, S; Jarnagin, K; Nelson, DB; Spelman, L; Gold, LF Stein
Atopic dermatitis (AD), a chronic, relapsing, inflammatory skin disease that is characterized by intense pruritus and eczematous lesions with up to 90% of patients presenting with mild to moderate disease. Current topical treatments for AD have not changed in over 15 years and are associated with safety concerns. In AD, overactivity of phosphodiesterase 4 (PDE4), leads to inflammation and disease exacerbation. Crisaborole Topical Ointment, 2%, is a novel, nonsteroidal, topical anti-inflammatory PDE4 inhibitor currently being investigated for the treatment of mild to moderate AD. Preliminary studies in children and adults demonstrated favorable efficacy and safety profiles. Crisaborole may represent an anti-inflammatory option that safely minimizes the symptoms and severity of AD and that can be used for both acute and long-term management.